Antimicrobial Activity of Some 1,3,4-Thiadiazole Metal Complexes - Ghudhaib, Kadhim K; Bakir, Shaimaa R; Hanna, Ekbal R (Al-Nahrain Journal of Science, 2014)
Biological activities of Cu (II), Pt (IV), Zn (II) and V (IV) metal complexes with 1, 3, 4 – thiadiazole derivatives towards pathogenic bacteria (Staph. aureus, Bacillus cereus, Pseudomonas aerogenosa and Escherichia coli) and the fungus Candida albicans were studied. The investigation was conducted using plate agar method. Sulfadiazine was used as standard drug in this study. The results were referred to that the biological activities of the studied compounds are more effective than sulfadiazine. The minimum effective dose of the studied compounds against of the named bacteria was 50µg/ml, while the minimum effective dose of sulfadiazine was 100µg/ml. Moreover, Candida albicans was affected by all the studied compounds at 50µg/ml, but there is no significant effect of sulfadiazine toward Candida albicans even at the highest dose, 200µg/ml.